Analisis Literasi Keuangan Terhadap Keberhasilan Usaha Mikro Kecil Dan Menengah (UMKM) Di Kota Malang Dengan Pemanfaatan Teknologi Digital Sebagai Variabel Moderasi - Bintang Prabowo; Noor Shodiq Askandar; Muhammad Tody Arsyianto (E-JRM : Elektronik Jurnal Riset Manajemen, 2026)
Abstract This study is motivated by the crucial importance of financial management and digital adaptation for the sustainability of Micro, Small, and Medium Enterprises (MSMEs) amid post-pandemic global economic competition. This study aims to analyze the effect of financial literacy on the success of MSMEs in Malang City, using digital technology as a moderating variable. Using a descriptive-verificative quantitative approach, data were collected through questionnaires from 150 MSME respondents selected through purposive sampling. Data analysis was performed using the Partial Least Square (PLS) method with SmartPLS 4.0. The results showed that financial literacy and the use of digital technology each had a positive and significant effect on business success. Furthermore, digital technology was found to significantly strengthen the relationship between financial literacy and MSME success. The implications of this study confirm that the integration of competent financial managerial capacity and the optimization of digital instruments are essential strategies for improving operational efficiency, competitiveness, and long-term business sustainability. Keywords: Financial Literacy, Digital Technology Utilization, Business Success, Malang City MSMEs